Targeted depletion of TRBV9+ T cells as immunotherapy in a patient with ankylosing spondylitis - Britanova, Olga V; Lupyr, Kseniia R; Staroverov, Dmitry B; Shagina, Irina A; Aleksandrov, Alexey A; Ustyugov, Yakov Y; Somov, Dmitry V; Klimenko, Alesia; Shostak, Nadejda A; Zvyagin, Ivan V; Stepanov, Alexey V; Merzlyak, Ekaterina M; et al. (Nature medicine, 2023)
Autoimmunity is intrinsically driven by memory T and B cell clones inappropriately targeted at self-antigens. Selective depletion or suppression of self-reactive T cells remains a holy grail of autoimmune therapy, but disease-associated T cell receptors (TCRs) and cognate antigenic epitopes remained elusive. A TRBV9-containing CD8+ TCR motif was recently associated with the pathogenesis of ankylosing spondylitis, psoriatic arthritis and acute anterior uveitis, and cognate HLA-B*27-presented epitopes were identified. Following successful testing in nonhuman primate models, here we report human TRBV9+ T cell elimination in ankylosing spondylitis. The patient achieved remission within 3 months and ceased anti-TNF therapy after 5 years of continuous use. Complete remission has now persisted for 4 years, with three doses of anti-TRBV9 administered per year. We also observed a profound improvement in spinal mobility metrics and the Bath Ankylosing Spondylitis Metrology Index (BASMI). This represents a possibly curative therapy of an autoimmune disease via selective depletion of a TRBV-defined group of T cells. The anti-TRBV9 therapy could potentially be applicable to other HLA-B*27-associated spondyloarthropathies. Such targeted elimination of the underlying cause of the disease without systemic immunosuppression could offer a new generation of safe and efficient therapies for autoimmunity.
Keywords: ankylózující spondylitida; T-lymfocyty; imunoterapie; receptory antigenů T-buněk; Epitopes; HLA-B Antigens; Immunotherapy; Tumor Necrosis Factor Inhibitors; Receptors, Antigen, T-Cell; T-Lymphocytes; epitopy; lidé; Spondylitis, Ankylosing; Humans; HLA-B antigeny; inhibitory TNF